2012
DOI: 10.1590/s0104-11692012000400016
|View full text |Cite
|
Sign up to set email alerts
|

Microcurrent application as analgesic treatment in venous ulcers: a pilot study

Abstract: This study aimed to evaluate the effect of microcurrent electrical stimulation on pain and area of venous ulcers. In a pilot study for a single-blind controlled clinical trial, carried out at an outpatient clinic during four weeks, 14 subjects with venous ulcers (mean age 62±9 years) were divided in two groups: microcurrent (n=8) and control group (n=6). Pain (by Visual Analogue Scale) and the ulcer area were measured by planimetry. There was a significant difference between the two groups with respect to pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
5
0
4
Order By: Relevance
“…A further single‐blinded RCT by Korelo et al. showed that although microcurrent ES significantly improved pain associated with venous leg wounds, it had no benefit on wound healing . However, they also had relatively small numbers and the treatment duration was only for 4 weeks.…”
Section: Direct Currentmentioning
confidence: 99%
“…A further single‐blinded RCT by Korelo et al. showed that although microcurrent ES significantly improved pain associated with venous leg wounds, it had no benefit on wound healing . However, they also had relatively small numbers and the treatment duration was only for 4 weeks.…”
Section: Direct Currentmentioning
confidence: 99%
“…Pain is a common symptom in patients with venous ulcers, which compromises the quality of life, due to the limitations of physical activities and provision for daily life activities, but adequate assistance can contribute to better understanding of pain and its reduction (15,(20)(21)(22) .…”
Section: Discussionmentioning
confidence: 99%
“…Com o aumento da longevidade da população mundial aumentaram-se também as doenças crônico-degenerativas, dentre elas as úlceras 1 . As úlceras, independentemente de sua etiologia, apresentam-se como lesões graves com perda circunscrita ou irregular da epiderme e/ ou derme, podendo atingir o tecido subcutâneo e seus tecidos subjacentes 2 .…”
Section: Introductionunclassified
“…Elas podem dividir-se em úlceras de perna (venosa, arterial, arteriovenosa, neuropática, neoplásica, metabólicas, hematológicas e infecto-parasitárias), úlceras de pressão (Grau I ao IV), úlceras por queimaduras, traumáticas, entre outras 2,3 .…”
Section: Introductionunclassified
See 1 more Smart Citation